Role of Cannabinoid Receptors in Psychological Disorder - Ambika Nand Jha; Dhaval M Patel (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Cannabinoid receptors, located throughout the body, are part of the endocannabinoid system. Cannabinoid CB1 and CB2 receptors are G protein-coupled receptors present from the early stages of gestation, which is involved in various physiological processes, including appetite, pain-sensation, mood, and memory. Due to the lipophilic nature of cannabinoids, it was initially thought that these compounds exert several biological effects by disrupting the cell membrane nonspecifically. Recent biochemical and behavioral findings have demonstrated that blockade of CB1 receptors engenders antidepressant-like neurochemical changes (increases in extracellular levels of monoamines in cortical but not subcortical brain regions) and behavioral effects consistent with antidepressant/antistress activity. We aim to define various roles of cannabinoid receptors in modulating signaling pathways and association with several pathophysiological conditions.